Fragmentasi Konstruksi Gender dan Kebangsaan dalam Sastra Indonesia Era Reformasi - Julia Suryakusuma (SUSASTRA: Jurnal Ilmu Susastra dan Budaya, 2006)
Women’s social values in post-Suharto Indonesia are marred by ambivalence, and even tainted by schizophrenia. How women are perceived is determined by may factors: class, ethnicity, religion, work, geographical location, etc. Due to the pluralistic character of Indonesia, we have been able to talk about ‘Indonesian women’ since a long time ago, let alone nowadays.The key to understanding today Indonesia is not merely diversity, but rather, fragmentation. This is inscribed in the constructions of gender, nation and ethnicity in literature, in which a ‘contestation of constructions’ which involves ‘sastrawangi’ writers, non-sastrawangi writers, chixklit, quasi-liberal women’s magazines, traditional and religious literature, popular literature from 1970s, as well as the official construction of women by the state, which remains dominant up to this point, and perhaps with an even more far reaching implication.